IMPACT OF ROBOTICS ON REDUCING HUMAN ERRORS IN LOGISTIC OPERATIONS - Gupta , Kali; Pradhan, Aadhyam; Vij, Simran (International Journal of Research -GRANTHAALAYAH, 2026)
In today's logistics operation there are some problems that every logistics sector faces like human fatigue requiring extra rest time, needing extra pay for overwork while in warehouses, not managing inventory properly, which leads to overstock and understock problems and human speed is limited compared to robots. Labour disputes and conflicts occur and mistakes occur in handling or recording data which can lead to wrong shipments etc. Automation and robotics are a good solution for the logistics sector. Because Automated Guided Vehicles (AGV) and Warehouse Automatic Machines (WAM) help in transporting inventory in a faster and more efficient way without any damage. Robotics helps in the whole logistics process, including safety material handling, packing, labelling, and order fulfilment. All this can be done in a smooth way with the help of robots and automatic machines. The tools used in this study are AGVs and RFID. Amazon and DHL are the best examples of companies that use them. The finding suggests that the role of automation and robotics in shaping logistics will create a huge impact, the logistics ecosystem will become faster, safer, and more sustainable. By highlighting opportunities and challenges. The study provides a roadmap for every logistic operation. The impact of robotics and automation are core drivers of future supply chain management.